Advances in immune mediated inner ear disease - Kullar, Peter; Santa Maria, Peter (Frontiers in Audiology and Otology, 2025)
Immune-mediated inner ear disease (IMIED) is emerging in our understanding as a cause of sensorineural hearing loss (SNHL). It poses a considerable diagnostic challenge due to the lack of specific tests and diagnostic biomarkers as well as clinical features that overlap with other audiovestibular disorders. Cases may involve isolated inner ear dysfunction or occur in the context of systemic autoimmune diseases. IMIED pathogenesis involves the interplay of autoantibodies, cytotoxic T cells, and innate immune mechanisms. Corticosteroid responsiveness is a defining feature of IMIED, but refractory cases may require alternative immunosuppressive agents. Although emerging immunosuppressive regimens demonstrate potential efficacy, larger trials are warranted to establish diagnostic and therapeutic guidelines. While symptomatic treatments including hearing aids and cochlear implants are beneficial in patients with IMIED associated hearing loss, future strategies focus on preventing irreversible inner ear damage and preserving hearing by developing innovative immunomodulatory strategies.